Characterization of intraoperative hemodynamic instability in patients undergoing general anesthesia - Ripollés-Melchor, Javier; Valbuena-Bueno, Miguel A.; Fernández-Valdés-Bango, Paula; Rodríguez-Herrero, Agustín; Tomé-Roca, José L.; Olvera-García, Mercedes; García-López, Daniel; Ruiz-Escobar, Alicia; Carrasco-Sánchez, Laura; Abad-Gurumeta, Alfredo; Lorente, Juan V.; Vargas-Berenjeno, Carmen A.; et al. (Frontiers in Anesthesiology, 2024)
Background: Intraoperative hypotension (IOH) has been associated with increased postoperative morbidity and mortality, emphasizing the importance of maintaining hemodynamic stability during general anesthesia. The Hypotension Prediction Index (HPI) is a recently developed tool obtained from the arterial pressure waveform for predicting the likelihood of hypotension and reflecting the level of hemodynamic instability (HI).In this retrospective observational cohort study, we analyzed anonymized data that were prospectively collected in patients having major abdominal surgery in six Spanish centers during 2022. We analyzed data from patients who underwent general anesthesia and required intraoperative monitoring with the Hemosphere monitoring system and HPI software. We defined five patterns of HI using a decision-making algorithm based on cardiovascular pathophysiology: absolute and relative hypovolemia, vasoplegia, and myocardial depression with and without vasoplegia.Results: After analyzing 2038 hours of hemodynamic monitoring from 393 patients, 1946 episodes of HI were identified. Vasoplegia was the most common type of HI, accounting for 50.1% HI episodes. Absolute and relative hypovolemia were the next most frequent types, contributing 30.7% and 15.5% of the HI episodes.We identified five distinct patterns of hemodynamic instability based on the evaluation of hemodynamic parameters underlying arterial hypotension during general anesthesia for patients undergoing major abdominal surgery. Vasoplegia was found to be the most frequent type. These novel classifications can help guide targeted treatment strategies for managing hemodynamic instability and reducing the risk of intraoperative hypotension. 4